Antibacterial efficacy of Salvadora persica as a cleansing teeth towards Streptococcus mutans and Lactobacilli colonies - Erlina Sih Mahanani; Mohd Fadhli Khamis; Erry Mochamad Arief; Siti Nabilah Mat Rippin; Zainul Ahmad Rajion (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Salvadora persica is a traditional chewing stick for cleaning teeth that it is known Siwak. Several studies have demonstrated the antimicrobial effects of Salvadora persica. Purpose: This study was aimed to examine the effectiveness of Salvadora persica in several modified preparation against the salivary Streptoccocus mutans and Lactobacilli. Methods: A single-blind, randomized clinical trial study with crossover design was used. The study comprised of 5 groups, per group consisted of 14 healthy dental students who had good oral hygiene. Each participant was given 5 intervention to clean their teeth using, electric toothbrush modified with siwak, electric toothbrush with siwak toothpaste (colgate kayu sugi toothpaste), electric toothbrush with general toothpaste (colgate total toothpaste), original siwak chewing stick and normal saline. The wash out periode each intervention was 3 days. Patients’ saliva was used to quantify the levels of Streptococcus mutans and Lactobacilli using caries risk test (CRT) kit from Vivadent. Results: The results showed that there was a reduction in Streptococcus mutans and Lactobacilli risk score after cleansing different intervention except electric toothbrush modified with siwak. However, there was no significant difference for Streptococcus mutans (p=0.158) and Lactobacilli (p=0.396) risk score reduction when comparison was done between the groups. Conclusion: The original siwak chewing stick has antimicrobial effects similar to toothbrushing with general toothpaste and salvadora persica toothpaste. However, electric toothbrush modified with siwak has no effect on microbial reduction.Latar belakang: Salvadora persica adalah pembersih gigi tradisional yang lebih dikenal dengan sebutan Siwak. Beberapa penelitian menunjukkan bahwa Salvadora persica memiliki daya antibakteri. Tujuan: Penelitian ini bertujuan untuk mengetahui efektivitas Salvadora persica dalam berbagai bentuk sediaan untuk membersihkan gigi terhadap bakteri Streptococus mutans dan Lactobacilli dalam saliva. Metode: Desain penelitian yang digunakan adalah single-blind, randomized clinical trial study dengan crossover. Lima kelompok perlakuan melakukan pembersihan gigi, tiap kelompok terdiri dari 14 mahasiswa kedokteran gigi, sehat dan memiliki kebersihan mulut yang baik. Tiap subyek diberi 5 macam perlakuan untuk membersihkan gigi menggunakan sikat gigi elektrik dimodifikasi dengan siwak, sikat gigi elektrik dengan pasta gigi mengandung ekstrak siwak (colgate kayu sugi), sikat gigi elektrik dengan pasta gigi umum (colgate total), siwak asli, dan salin. Saliva pasien digunakan untuk menganalisa pengurangan banyaknya bakteri Streptococcus mutans dan Lactobacilli sebelum dan sesudah perlakuan menggunakan Caries Risk Test (CRT) dari Vivadent. Hasil: Hasil menunjukkan adanya penurunan skor Streptococcus mutans dan Lactobacilli setelah pembersihan gigi dibandingkan sebelumnya. Sementara itu tidak ada perbedaan signifikan terhadap penurunan skor Streptococcus mutans (p=0.158) dan Lactobacilli (p=0.396) ketika dibandingkan antar kelompok. Kesimpulan: Mengunyah kayu siwak mempunyai efek antimikrobial yang hampir sama dengan menyikat gigi menggunakan kombinasi pasta gigi biasa dan pasta gigi yang mengandung siwak, akan tetapi meyikat gigi dengan sikat elektronik yang dimodifikasi dengan siwak dapat menurunkan jumlah bakteri.